2020
DOI: 10.31235/osf.io/kn6af
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Queering Asylum in Europe: A Survey Report

Abstract: This report discusses the data gathered through two surveys carried out in the context of the SOGICA project. SOGICA – Sexual Orientation and Gender Identity Claims of Asylum: A European human rights challenge – is a four-year (2016-2020) research project funded by the European Research Council (ERC) that explores the social and legal experiences of people across Europe claiming international protection on the basis of their sexual orientation or gender identity (SOGI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Twenty-four applicants attended school for less than 12 yr, eight for less than 9 yr and 24 for less than 6 yr. This is a different landscape than the one in many other European countries where asylum seekers have obtained a higher level of education (Andrade et al, 2020). A possible explanation of this phenomenon is that in general Greece is not considered a desirable destination among refugees and consequently refugees who belong to an upper social class can afford the longer journey toward richer countries.…”
Section: Ignoring the Intersection Of Sexuality With Classmentioning
confidence: 93%
“…Twenty-four applicants attended school for less than 12 yr, eight for less than 9 yr and 24 for less than 6 yr. This is a different landscape than the one in many other European countries where asylum seekers have obtained a higher level of education (Andrade et al, 2020). A possible explanation of this phenomenon is that in general Greece is not considered a desirable destination among refugees and consequently refugees who belong to an upper social class can afford the longer journey toward richer countries.…”
Section: Ignoring the Intersection Of Sexuality With Classmentioning
confidence: 93%
“…These relate mainly to the discretion requirement and disbelief towards asylum applicants as being LGBTQI+ (e.g. Andrade et al, 2020;Berg and Millbank, 2013;Dustin and Held, 2018;Millbank, 2009). In addition, identity-based questions often disregard the particular discourse and practice in non-Western countries, where identification with a particular social group often follows other paths.…”
Section: Problematic Legal Framework: Gender Identity and Expression In Refugee Lawmentioning
confidence: 99%
“…However, what arose in this report in contrast to the "Fleeing Homophobia" report is that issues related to the country of origin of LGBTI+ claimants have become a central part of their struggles. Respondents from organizations supporting LGBTI+ asylum seekers reported that accurate country of origin information was often unavailable; and when asked about the differences they perceived in the treatment of LGBTI+ asylum claims, "country of origin" was reported as the primary factor legitimizing such differences (Andrade et al, 2020).…”
Section: Gender-sensitive Safeguards To "Safe Country" Practices: a Stalematementioning
confidence: 99%
“…The lack of appropriate LGBTI-specific country of origin information has been signaled as particularly problematic in recent years (Jansen, 2014;Andrade et al, 2020). Several of the organizations interviewed reported submitting country of origin reports for the claimants they were supporting to complement the partial information possessed by asylum authorities.…”
Section: Legitimizing Informal Practices Of Ex Ante Exclusionmentioning
confidence: 99%
See 1 more Smart Citation